Conflict and politicized religion: The case of a study on electoral democracy in Jambi Province - Maria Goreti Silitonga; Muliono Muliono; Hatta Abdi Muhammad (Privietlab, 2025)
This study aims to reveal the conflicts based on intolerance and politicized religion in the electoral democracy process that is developing in Jambi Province. This study is critical because the phenomena reflect a relationship between social and political groups in the threat of disharmony and polarization. This study employed qualitative methods. Data were collected through observations and in-depth interviews. Data analysis was performed through data reduction, data display, and conclusions that were analyzed using the theory. The results of this study show that social conflict is rooted in intolerance and politicized religion. Second, intolerance in Jambi Province is manifested as discrimination against minority groups based on religious values. Third, the politicization of religion at the grassroots level during the electoral democracy process is a crucial factor in conflicts that threaten social rifts. Specifically, the issue of intolerance and conflict in Jambi Province can be formulated through three main interrelated contexts: intolerance based on religious values, social conflict, and political identity. This study is expected to contribute to the study and reveal the reality of intolerance and socio-political conflict that tends to be hidden in the local community landscape both in Jambi Province and other regions in Indonesia.